Gender and preferences at a young age: Evidence from Armenia - Khachatryan, Karen; Dreber, Anna; von Essen, Emma; Ranehill, Eva (Journal of Economic Behavior and Organization, 2015)
We look at gender differences in competitiveness, risk preferences and altruism in a large sample of children and adolescents aged 7–16 in Armenia. Post-Soviet Armenia has few formal barriers to gender equality but is also characterized by a patrilineal kinship system and traditional gender roles. In contrast to research conducted in Western countries, we find that girls increase their performance more than boys in response to competition in a running task. We find no gender differences in the other three tasks we explore: skipping rope, a mathematical task, and a verbal task. We also find no difference in the willingness to compete in either the mathematical or the verbal task. In line with previous research, we find that boys are less altruistic and more risk taking than girls, and that the latter gap appears around the age of puberty.
Keywords: Competitiveness; Risk preferences; Altruism; Children; Gender differences; Experiment; C91; D03; J16